Keragaman Nukleotida Gen Lcy-b (Lycopene beta cyclase) Kultivar Tomat Betavila F1, Fortuna F1 dan Tymoti F1 - Muhammad Thoifur Ibnu Fajar; Purnomo P; Niken Satuti Nur Handayani (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Tomato has three lycopene gene, namely lycopene beta cyclase (Lcy-b), lycopene beta-cyclase kromoplas (Cyc-b) and lycopene epsilon cyclase (Lcy-e). Lcy-b gene can be used as determinant of phylogenetic relationship between tomato and chili. This research aims to know phylogenetic relationship among tomatoes cultivar, namely Betavila F1, Fortuna F1 and Tymoti F1, then phylogenetic relationship between these tomatoes cultivar and tomatoes sequences Kristin KC140137.1, Darsirius KC140135.1, Pennellii XM 015217853.1, Villosum KP313876.1 and outgroup Capsicum annuum GU085266.1. Besides that, this research also aims to know the difference of nucleotide among tomatoes cultivar and the others tomato sequences and the outgroup Capsicum annuum based of alignment result. PCR (Polymerase Chain Reaction) method and NCBI primer design used to isolate Lcy-b gene. Acquired sequences were analyzed by Mega 6 and Clustal X softwares. The result of phylogenetic relationship among tomatoes cultivar showed Betavila F1 cultivar closely related to Tymoti F1 cultivar and Fortuna F1 cultivar closely related to Tymoti F1 cultivar. Phylogenetic relationship between tomatoes cultivar and the other tomatoes sequences showed Fortuna F1 cultivar closely related to Darsirius cultivar and varieties Pennellii, Betavila F1 cultivar distantly related to the other tomatoes sequences, and Tymoti F1 cultivar closely related to Kristin cultivar. The difference of nucleotide were found at Pennellii tomato that is 1 nucleotide with transition mutation, found at Villosum tomato that are 12 nucleotides with transition and transversion mutation, and found at Capsicum annuum that are 16 nucleotides with transition and transversion mutation. Phylogenetic relationship using Lcy-b gene expected to be used as a transgenic strategy to modify carotenoid content that improves tomatoes nutrition